2015
DOI: 10.1111/ijd.13165
|View full text |Cite
|
Sign up to set email alerts
|

Learning from mistakes: errors in approaches to melanoma and the urgent need for updated national guidelines

Abstract: Based on the present results, we propose that in countries lacking national guidelines, clinicians should adhere to international evidence-based guidelines for the diagnosis and treatment of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…[26][27][28] Despite all efforts in research, although skin cancer diagnosis is usually not difficult in typical cases, early detection remains challenging to this day. 29,30 This study shows that phenotypic traits are the best candidates to become screening markers for skin cancer risk and that this risk could be instantly evaluated at first glance, using three parameters of the anatomy of the iris, irrespective of the reason that brings a patient to the clinician's office.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[26][27][28] Despite all efforts in research, although skin cancer diagnosis is usually not difficult in typical cases, early detection remains challenging to this day. 29,30 This study shows that phenotypic traits are the best candidates to become screening markers for skin cancer risk and that this risk could be instantly evaluated at first glance, using three parameters of the anatomy of the iris, irrespective of the reason that brings a patient to the clinician's office.…”
Section: Discussionmentioning
confidence: 97%
“…There has been an increasing focus on screening, primary prevention and early detection in skin cancer worldwide in the last decade, with a high number of studies on self‐assessment questionnaires, risk factor analysis, total body skin examination emphasis and even more complex computer‐aided risk assessment tools . Despite all efforts in research, although skin cancer diagnosis is usually not difficult in typical cases, early detection remains challenging to this day …”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the results of this study was obtained significant evidence for SPSM process of systems weaknesses within the context of the health care organization. Preservation specimen integrity and antigenicity in pathology specimens is the essential stair in comletely diagnoses and 10% neutral buffered formalin (NBF) has been a traditional preservative [12,13]. Preservation of the specimen helps prevent decomposition, inhibit microbial growth, and prevent autolysis [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature shows 13 previously reported cases of pigmented lesions initially treated cosmetically with cryotherapy and/or laser treatment, later diagnosed as LM/LMM [8,[22][23][24][25][26] ( Table 2). The ages range from 59 to 72, with seven males and six females.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 13 reported cases, 8 were found to have invasive LMM (61.5%) on final excision and one patient had lymph node metastasis. Additional reports document other forms of melanoma, including nodular, amelanotic, and metastatic, occurring after prior laser or cosmetic treatment of presumed benign lesions [24][25][26][27][28]. Stankiewicz et al describe three patients who presented for cosmetic removal of pigmented lesions, two referred by physicians, all found to be LM or melanoma in situ before any cosmetic intervention, underscoring the importance of careful evaluation of presumed benign pigmented lesions before treatment [5].…”
Section: Discussionmentioning
confidence: 99%